PICTURE OF BODY SHAMING & SELF CONFIDENCE OF STUDENTS : GAMBARAN BODY SHAMING & KEPERCAYAAN DIRI MAHASISWA/I DI PEKANBARU - Hazrina Adelia; Selvi Selvi; Putri Wulandini S (LPPM Universitas Abdurrab, 2025)
Adolescence is a transitional period that makes it easy for teenagers to follow and be carried away by the changes that occur, such as lifestyle trends that are widely developing among teenagers, not a few teenagers who start body shaming or bullying for those who do not follow or are considered not in accordance with the trend. This action can have a negative impact on victims of body shaming, namely it can affect a person's mental and social conditions. Among them can make victims have a bad assessment of themselves so that victims become insecure. The purpose of this study was to determine the Picture of Body Shaming & Self-Confidence of Students University in Pekanbaru. This type of research is quantitative research with a descriptive design. The population in this study were all students of in University Pekanbaru, totaling 1,583 people. The sampling technique used the cluster sampling technique. Data were collected using a questionnaire. Data analysis using univariate analysis. The results of the study obtained Body Shaming of Students with the category Done as many as 320 respondents (100%) followed by Self-Confidence the number of respondents with the High category as many as 320 respondents (100%).